PENDAMPINGAN PENERAPAN MINYAK IKAN SIDAT DALAM MENINGKATKAN KESEHATAN DAN GIZI SERTA STRATEGI BRANDING INOVATIF PRODUK BERBASIS LOKAL - Salim, Muhammad Agus; Wulansari, Nuni; Hendrawan, Arief; Prastowo, Muhammad Yogie (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to implement the utilisation of eel fish oil (Anguilla spp.) as a health supplement and nutritional enhancer for the community, as well as to develop innovative branding strategies for locally based products in Kaliwungu Village. Eel fish oil is recognised for its high concentration of omega-3 fatty acids, including DHA and EPA, which are highly beneficial for supporting heart health, brain development, and enhancing the immune system. However, this potential has not been optimally utilised by the local community, despite the abundant eel fish resources in Kaliwungu Village. The activities were carried out in several stages, including educating the community about the health benefits of eel fish oil, training in simple extraction techniques based on appropriate technology, and assisting in product packaging and marketing. In addition, the implementation team developed a branding strategy that highlights local value, product uniqueness, and sustainable economic potential. This approach was implemented through training in label design, brand naming, and the use of social media to expand market reach. The program's results showed increased community knowledge about the nutritional benefits of eel fish oil, improved technical skills in production processes, and enthusiasm for developing value-added local products. Eel fish oil products with local branding have now begun to be marketed within the village and surrounding areas. This program is expected to serve as a model for sustainable, local, potential-based economic development and to promote a healthy lifestyle through the utilisation of local biological resources.